The Effect of Using Blog in Writing Procedure Text - Nonita, Desi; Kardena, Absharini (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
This study was due to several problems related to the Learning English in writing. The problem was low daily test in writing on procedure text. Hereby, this study aimed to find out whether there was significant difference the students’ score procedure text in the control class and in the experimental class after using blog. Furthermore, this study used quasi experimental design. Then, the total sample was 37 students taken from class XI ITT as experimental class and XI IPS as control class of MA.KM Muhammadiyah. Moreover, the result of this study showed that the calculation of post-test of both classes, experiment class and control class was as follow, it obtained that the t-obtained (2.171) which was higher than the t-table (2.030) with degree of freedom (df) = 35. The alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected which meant that there was significant difference score writing in the control class and in the experimental class after using blog. It proved that using blog as writing could help the students in improving their ability in writing. This blog could be used as an alternative tool and it hoped that this blog improved students' abilities, especially on procedure text.